Does Early Bilingual Acquisition Affect Hemispheric Preferences during Simultaneous Interpretation? - Hamers, Josiane; Lemieux, Sylvie; Lambert, Sylvie (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2002)
AbstractBased on data from an earlier study (Lambert 1993), and on a propositional approach developed by Lemieux (1995), who refined quality of interpretation measurements sufficiently to determine a right-ear superiority at the beginning of a message and a left-ear superiority at the end of a message, the present study went one step further to examine the role played by experience, age and age of bilinguality, all possible factors influencing the hemispheric control of interpretation. Results indicated that the number of years of experience influences the quality of interpretation in that the more experienced interpreters interpreted better, regardless of ear of input. But overall results point to the possibility that hemispheric preferences for linguistic analysis might be much more under an interpreter’s voluntary control than first anticipated.